The Development of Nearpod Interactive Multimedia Using Problem Based Learning Models on Civics Learning in Elementary School - Katherine Putri Rivelia; Reinita Reinita (Universitas Pahlawan Tuanku Tambusai, 2023)
The rapid development of the times has made many changes in various sectors. There are more facilities and conveniences that can be used in learning. But in reality, the media used by teachers in learning is only limited to showing videos or PPT through infocus. It makes students less active and less participate in the learning process. The aim of this research is to develop nearpod interactive multimedia using problem-based learning model that is valid and practical for use on civics learning in grade IV SD.This research uses the 4D model with four stages, namely define, design, develop, and disseminate. Data were obtained from validation questionnaires and practicality questionnaires. The subjects of this study were 3 expert validators, 1 teacher, and 26 fourth grade students of SDN 24 Ujung Gurun. The validity test results obtained 90% material validation, language validation obtained 88%, media validation obtained 98% with a very valid category. Furthermore, the results of the practicality of student responses obtained 91% and teacher responses of 96% with a very practical category. The results of this study indicate that the use of nearpod interactive multimedia with a problem-based learning model can increase student participation in learning Civics in Class IV elementary schools and thus improve the quality of learning.